(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
How can we create performative practices that produce physical and mental health? This was the guiding question of the project “Poetics of care: art in times of crisis”, carried out by the Research Group “Contemporary Performative Practices” in partnership with the Performers without Borders, at UNIRIO. Through actions, meetings, studies and performances, we investigated experimentally and cartographically the intersections between performative practices and health practices. During the research, seven axes were explored, which are presented in this article. In their various combinations in performance art pieces, these axes configure a type of performative practices which, according to the theoretical framework mobilized, we call “Poetics of Care”.